Financial Accountability in Village-Owned Enterprises Governance: Akuntabilitas Keuangan dalam Tata Kelola Perusahaan Milik Desa - Sari, Dwi Navila; Widodo, Heri (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Village-Owned Enterprises (BUMDes) are vital instruments for local economic growth and community self-reliance. Specific Background: Many BUMDes face challenges in financial management, accountability, and transparency, impacting their operational sustainability. Knowledge Gap: Previous research often focuses on financial performance but rarely integrates governance and community participation perspectives. Aims: This study evaluates BUMDes’ financial management efficiency and accountability practices across several Indonesian villages. Results: The analysis shows that proper financial documentation, accounting system application, and adherence to SAK-ETAP standards significantly improve financial control and public trust. Novelty: The research links financial governance frameworks with community empowerment models for sustainable BUMDes performance. Implications: Strengthening internal control, transparency, and training for village officials can optimize local revenue generation and community welfare. Highlights: Financial transparency strengthens BUMDes performance. Accountability builds trust and village participation. Governance training improves financial efficiency.